Permafrost im periglazialen Westgrönland - Stäblein, Gerhard (ERDKUNDE, 1977)
The formation and distribution of permafrost is illustrated by examples from the environs of Holsteinsborg (66°56’ N / 54°20’ W) and Jakobshavn (69°13’ / 51°03’ W) in Western Greenland. The ecological and climatic conditions are discussed. Beneath the summer thaw layer, both areas show in places permanently frozen soil below depths of 20 and 130 cm respectively. Field studies have shown that in both areas the local petrographic, edaphic and ecological conditions are more important for the occurrence or cessation of permafrost than the regional climatic differences between the two areas. The area of continuous permafrost first begins on the coast further north near Upernavik (72°47’ N). Two GGU stations with series of ground temperature measurements covering several years are used to illustrate the differences in temperature distribution by means of pedothermoisopleths. The correlation to the parameters of modal temperatures and snow covering is investigated.